2020
DOI: 10.1177/0192513x20948919
|View full text |Cite
|
Sign up to set email alerts
|

“I Should Get Married as Soon as Possible, but the Relationships I Start Do Not Work”: Marital Prospects of Ethiopian Female Return Migrants from the Arabian Gulf

Abstract: This study seeks to understand how the intersection of migration, gender, and age shapes the marital prospects of Ethiopian female domestic workers returning from the Arabian Gulf and the Middle East. The study found that gendered attitudes in Ethiopian society rooted in patriarchy interact with age and the migration experiences of returnees to create stigma and marginalization, excluding the returnees from the highly desired social institution of marriage. It was also found that returnees tended to dissociate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As a result, their husbands do not want to maintain regular relations with them. Thus, the forced return has a negative impact on the RMWs’ marital relationships (Ahmed et al, 2015; Nisrane et al, 2021).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, their husbands do not want to maintain regular relations with them. Thus, the forced return has a negative impact on the RMWs’ marital relationships (Ahmed et al, 2015; Nisrane et al, 2021).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In this situation, some unmarried returnees leave their family and live alone in another place after return. Thus, the unmarried RMWs prefer to stay separately from family and society to avoid non-acceptance from the family and negative attitudes and stigma from society (Nisrane et al, 2021).…”
Section: Key Challenges Of Reintegrationmentioning
confidence: 99%
“…Migration experience generally has negative impacts on the marital prospects of unmarried women (Nisrane et al, 2020;Ullah, 2013). Migration also affects immigrants' integration into destination countries (Belanger & Rahman, 2013;Nisrane et al, 2020).…”
Section: Uncertainty Of Lifementioning
confidence: 99%
“…Migration experience generally has negative impacts on the marital prospects of unmarried women (Nisrane et al, 2020;Ullah, 2013). Migration also affects immigrants' integration into destination countries (Belanger & Rahman, 2013;Nisrane et al, 2020). In addition, research have shown that the psychological trauma of sexual violence experienced by women during migration, among the married or unmarried, affects reintegration in their country of origin (Ketema, 2014).…”
Section: Uncertainty Of Lifementioning
confidence: 99%